Food Contamination by Packaging / Migration of Chemicals from Food Contact Materials - Garcia Ibarra Veronica; Lestido Cardama Antia; Rodriguez Bernaldo De Quiros Ana; Sendon Raquel (De Gruyter, 2019)
This book will be of interest to students and researchers in universities and research institutions associated with food packaging and, in general, to the food safety sector. Preface, Acknowledgements, Introduction, Bisphenol A, Melamine, Phthalates and Alternative Plasticizers, Photoinitiators, Other Chemical Substances from Food Contact Materials, Non-Intentionally Added Substances, Estimation of Exposure to Migrants from Food Contact Materials, Index.